2015
DOI: 10.1007/s10644-015-9161-y
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment and regional economic development in Russia: an econometric assessment

Abstract: Abstract:In this paper, we estimate the effect of foreign direct investment (FDI) on total factor productivity (TFP) in Russian regions, paying special attention to the country's investment boom and the remarkable regional gaps in terms of cumulative direct investments in and after 2003. We also examine possible synergistic effects between FDI and local R&D potential to test the absorptive capacity hypothesis. Our estimation results strongly suggest the remarkable role of FDI in the regional economic developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 46 publications
(47 reference statements)
2
25
0
Order By: Relevance
“…In line with Ledyaeva and Linden () and Iwasaki and Suganuma (), FDI had a positive influence on the economic growth in Russian regions although, as these authors indicate, this effect is subject to the regions’ absorptive capacity. Indeed, FDI is a critical channel for knowledge diffusion in Russia: a rise in the share of FDI in GRP by 1 pp increases the rate of growth of GRP per capita by 0.100–0.103 pp.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…In line with Ledyaeva and Linden () and Iwasaki and Suganuma (), FDI had a positive influence on the economic growth in Russian regions although, as these authors indicate, this effect is subject to the regions’ absorptive capacity. Indeed, FDI is a critical channel for knowledge diffusion in Russia: a rise in the share of FDI in GRP by 1 pp increases the rate of growth of GRP per capita by 0.100–0.103 pp.…”
Section: Resultssupporting
confidence: 70%
“…The role of foreign direct investment (FDI) as a critical channel for knowledge diffusion in Russia was studied by Untura () and Ledyaeva, Karkhunen, Kosonen, and Ponomarev (); the hypothesis that Russia's performance was influenced by the utilization of the knowledge tested by Ahrend (), Brock (), Ledyaeva and Linden (), Ledyaeva et al (), and Iwasaki and Suganuma (). They demonstrated that FDI from developed countries is related to the purchase of novel and high‐tech equipment to a greater extent than FDI from developing countries (Naumova & Oleynik, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results support the important role played by foreign direct investment in promoting productivity growth, which proves to be robust to several alternative specifications. Iwasaki and Suganuma (2015) estimated the remarkable role of FDI in regional economic development in Russia. They found that the positive effect of FDI on total factor productivity (TFP) may increase in regions that received larger amounts of foreign capital.…”
Section: The Overview Of Factors Of Regional Economic Growthmentioning
confidence: 99%
“…Various empirical studies conducted in Russia, Eastern Europe, China and other countries show the important role of investment in regional economic development. In particular, foreign direct investment has a positive effect on economic growth, labor productivity and the development of innovation (Dairabayeva et al 2016, Hafner and Kleinert 2018, Iwasaki and Suganuma 2015.…”
Section: Introductionmentioning
confidence: 99%